2012
DOI: 10.1002/suco.201100012
|View full text |Cite
|
Sign up to set email alerts
|

Formwork pressure induced by highly flowable concretes – design approach and transfer into practice

Abstract: An analytical model for the calculation of the pressure of concrete on vertical formwork has been developed on the basis of experimental tests on highly flowable concretes in the fresh state (see companion paper “Material investigations and large‐scale tests”). The model takes into account the time‐dependent material parameters of the fresh concrete, the specific properties of the highly flowable vibrated concretes and self‐compacting concretes (SCC) as well as operational aspects. A proposal for the design of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 4 publications
0
17
0
1
Order By: Relevance
“…Aus Versuchsergebnissen [13,14] mit einer sogenannten Kombinierten Versuchseinrichtung (KVA) [15] an Betonen der Konsistenzklasse F5 und F6 wurden Funktionen des Seitendruckbeiwerts als Mittelwerte in Abhängigkeit von der Zeit λ i,MW (t/t E,eff ) für eine nachgiebige Schalung abgeleitet (vgl. Gln.…”
Section: Implementierte System-und Materialparameterunclassified
“…Aus Versuchsergebnissen [13,14] mit einer sogenannten Kombinierten Versuchseinrichtung (KVA) [15] an Betonen der Konsistenzklasse F5 und F6 wurden Funktionen des Seitendruckbeiwerts als Mittelwerte in Abhängigkeit von der Zeit λ i,MW (t/t E,eff ) für eine nachgiebige Schalung abgeleitet (vgl. Gln.…”
Section: Implementierte System-und Materialparameterunclassified
“…After mixing, the concrete was placed in the sample holders. The normal pressure was increased incrementally until the final setting state (Proske 2007;Graubner et al 2012).…”
Section: Measurement Of Frictionmentioning
confidence: 99%
“…Some of these phenomena are directly related to the friction between the materials in contact. The friction at the concrete/formwork interface can be considered a favourable factor that reduces lateral pressure exerted on the formwork, but it can also be unfavourable to the quality of the concrete surfaces (Proske et al 2010;Graubner et al 2012;Libessart 2006;Kwon et al 2011). Some studies have reported on the effect of friction on formwork pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a number of models for predicting lateral pressure of SCC have been developed worldwide [4][5][6][7][8][9][10][11][12][13][14]. Some of them are phenomenological and others are developed by empirical testing in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…would lead to increased formwork system costs or risks of form deformation or eventual collapse. However, the literature has repeatedly shown that lateral pressure is considerably lower than the hydrostatic pressure when casting SCC [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%